Caring-Based Psychosocial Intervention Associated with Reduced Diabetes Burnout Among Older Adults with Type 2 Diabetes - Ummu Muntamah; Maksum; Wulansari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Diabetes burnout is a significant psychosocial challenge among older adults with type 2 diabetes, contributing to emotional exhaustion, maladaptive coping, and reduced quality of life. Conventional diabetes management programmes often emphasise biomedical outcomes while insufficiently addressing psychosocial needs. This study examined whether a caring-based psychosocial approach integrated into a community diabetes programme was associated with reduced diabetes burnout and improved coping mechanisms and quality of life among older adults with type 2 diabetes. Methods: A quasi-experimental pretest-post-test control-group study was conducted among 176 older adults with type 2 diabetes enrolled in PROLANIS at primary healthcare centres in Semarang Regency, Indonesia. The intervention group received a four-week caring-based psychosocial programme delivered weekly by trained healthcare providers, focusing on empathetic communication, emotional support, autonomy support, coping-skills training, and family involvement. The control group received standard PROLANIS education. Diabetes burnout, coping mechanisms, and quality of life were assessed using validated instruments. Between-group differences were analysed using comparative tests and analysis of covariance (ANCOVA), with adjustment for baseline scores. Results: Participants receiving the caring-based psychosocial intervention demonstrated significantly greater reductions in diabetes burnout and greater improvements in coping mechanisms and quality of life than participants in the control group (all p < 0.001). Mean burnout scores decreased more in the intervention group (Δ = -16.88 vs -11.73), while coping scores (Δ = 38.28 vs 22.41) and quality-of-life scores (Δ = 40.20 vs 11.77) increased more substantially. ANCOVA confirmed significant between-group differences after adjustment for baseline values. Conclusion: Integration of a caring-based psychosocial intervention into community diabetes management was associated with reduced diabetes burnout and improved psychosocial outcomes among older adults with type 2 diabetes. Empathetic communication, emotional support, coping facilitation, autonomy support, and family involvement may enhance psychosocial adaptation and well-being in ageing populations. Further randomised longitudinal studies are needed to confirm long-term effectiveness and underlying mechanisms.